Living Islam: Study of the “Pintan” Tradition in Welcoming and Ending the Month of Ramadhan: Living Islam: Studi Atas Tradisi “Pintan” Dalam Menyambut dan Mengakhiri Bulan Ramadhan - Rahmat Fauzi; Dinda Alfa Regina (Institut Agama Islam Negeri Kerinci, 2022)
The reception of Islamic societies to authoritative sources of Islamic teachings can be diverse. However, in the history of Islamic civilization, scholars have exerted more of their intellectual efforts to study the informative rather than the performative function of the Islamic scripture. Living Islam pointing to a new sub-field within Islamic studies that focuses on the Qurʾanic and hadith reception in society as imprinted in the socio-cultural life of the Muslim community. This article discusses the tradition of pasang Pintan as the phenomenon of Living Islam in the Javanese Muslim community, Patok Village, Kayu Aro, Kerinci. This study aims to examine how the community's understanding and reception of the source of Islamic teachings and how it was reflected in the tradition of Pasang Pintan. This tradition is categorized as a Living Islam phenomenon because it has particles and dimensions of Islam in it and has been deeply rooted in the socio-cultural of the community. In addition, this tradition is considered to have a normative foundation derived from both the Quran and hadith. Using qualitative methods and phenomenological approaches, this study found that the tradition of pasang Pintan by the Patok Village community has a functional-cultural meaning, namely as a form of unification between religion and culture. In addition, Pintan is intended as a means of filial piety to parents and social cohesion, enlivening the month of Ramadhan, do'a and zikir, as well as a medium of moral education, especially to parents.